2022
DOI: 10.3390/nano12071198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic and Photokilling Activities of Cu-Doped TiO2 Nanoparticles

Abstract: In this work, metal-doped titanium dioxide (TiO2) was synthesised with the aim of improving photocatalytic degradation and antimicrobial activities; TiO2 was doped with copper (Cu) ranging from 0.1 to 1.0 wt%. The physical and chemical properties of the Cu-doped TiO2 nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), the Brunauer–Emmett–Teller method (BET) and diffuse reflection spectroscopy (DRS). The results revealed that the anatase phase of TiO2 was maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Sunada [62] showed that the synergistic action of the photocatalytic activity of TiO 2 and that of copper ions produced a bactericidal impact of the Cu/TiO 2 combination even on copper-resistant E. coli cells under very low UV irradiation. Cu-doped TiO 2 showed superior antibacterial activity against E. coli when compared to undoped TiO 2 , as reported by Mingmongkol et al [63]. However, the high Cu doping concentrations of 1.0 wt.% and Cu-doped TiO 2 exhibited detrimental effects on the charge transfer, •OH generation, and surface charge of the nanoparticles.…”
Section: Combinations Between Copper Copper Oxide and Other Nanoparti...supporting
confidence: 66%
“…Sunada [62] showed that the synergistic action of the photocatalytic activity of TiO 2 and that of copper ions produced a bactericidal impact of the Cu/TiO 2 combination even on copper-resistant E. coli cells under very low UV irradiation. Cu-doped TiO 2 showed superior antibacterial activity against E. coli when compared to undoped TiO 2 , as reported by Mingmongkol et al [63]. However, the high Cu doping concentrations of 1.0 wt.% and Cu-doped TiO 2 exhibited detrimental effects on the charge transfer, •OH generation, and surface charge of the nanoparticles.…”
Section: Combinations Between Copper Copper Oxide and Other Nanoparti...supporting
confidence: 66%
“…Although the experimental evidence for the enhancement in photocatalytic activity in TiO 2 through copper doping is inconclusive, copper doping can modify the large bandgap of TiO 2 to optimize its optical properties for visible-light harvesting. Mingmongkol et al doped TiO 2 with Cu ranging from 0.1 to 1.0 wt.%, which resulted in the bandgap decreasing from 3.20 eV for undoped TiO 2 to 3.12 eV for 1.0 wt.% Cu-doped TiO 2 [ 26 ]. Mathew et al reported that the visible light absorption property of Cu-TiO 2 increased and the band gap reduced to 2.8 eV with 0.5 mol% Cu [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These nanocomposites are commonly employed as nano delivery systems that improve bioavailability, biodistribution, and preferentially localizing diseased tissues while protecting healthy tissues. However, because of their chemical nature, many metal ion (TiO 2 /CuO) based nanoparticles also demonstrate effective antibacterial activity [ 30 , 31 ]. The antibacterial potential of a Berberis vulgaris plant extract against microorganisms linked with caries, such as Streptococcus spp.…”
Section: Introductionmentioning
confidence: 99%